Marital Stress, Antenatal Anxiety, Social Support, and Postnatal Depression among Nursing Mothers in Ibadan - Okhakhume, A. S.; Sunday, Shide; Osuagwu, Angela I. (Advances in Social Sciences Research Journal, 2017)
Postnatal depression is a mental health disorder afflicting between 15-18 percent of new mothers in Nigeria. Depressive symptoms and actual depression affects the psychological and social wellbeing of the affected mothers, their new infants, husbands and family members. Consequently, this study examined the effect of marital stress, antenatal anxiety, and social support on postnatal depression among nursing mothers in Ibadan. The study used an ex-post factor survey research design. A total of 128 nursing mothers (N=128; % = 98.4) were administered questionnaire in Ibadan. The participants’ average age was 29.68 years. Results revealed that antenatal anxiety has a significant correlation with postnatal depression (P<.05). Also, separate social support was found to have an inverse correlation with postnatal depression (r = .047); marital stress has a positive correlation with postnatal depression (r = .108). Also, finding showed that antenatal anxiety has a significant independent influence on postnatal depression (β=230; t = 2.633; P=<.05) and there was a joint influence of marital stress, antenatal anxiety and social support on postnatal depression (R2 = .070, F = 3.128, P<.05) with a 7% variability. Social support mediates the influence of antenatal anxiety on postnatal depression (r=.239) while family structure has a significant independent influence on postnatal depression (β=.266;t=2.880; P=<.05). Psychological interventions and assessment of the independent and joint risk factors that are related to postnatal depression in nursing mothers be undertaken in hospitals with the aim of reducing the overall impact of these risk factors on postnatal mothers.